Front Cover: Phosphonate as a Stable Zinc‐Binding Group for "Pathoblocker" Inhibitors of Clostridial Collagenase H (ColH) (ChemMedChem 8/2021). (22nd April 2021) - Voos, Katrin; Schönauer, Esther; Alhayek, Alaa; Haupenthal, Jörg; Andreas, Anastasia; Müller, Rolf; Hartmann, Rolf W.; Brandstetter, Hans; Hirsch, Anna K. H.; Ducho, Christian
Abstract : The Front Cover shows work on inhibitors of bacterial collagenases. The inhibition of these virulence factors would reduce bacterial pathogenicity, thus furnishing a potential "pathoblocker". Previously reported inhibitors of zinc‐dependent collagenases employed a thiol function as zinc‐binding group (ZBG). The researchers have now identified a phosphonate unit to be a useful alternative ZBG that is stable towards oxidation. This paper reports on the favourable in vitro and in vivo properties of such a phosphonate‐derived collagenase inhibitor. More information can be found in the Full Paper by Anna K. H. Hirsch, Christian Ducho et al .